Perancangan Mesin Pengupas Singkong dengan Metodologi NIDA-QFD untuk Industri Keripik Singkong ABC Banyuwangi - Nurcahyo, Adib; Hidayah, Asfarina; Hamid, Abdul (Universitas Kadiri, 2024)
Banyuwangi produces potential cassava chips. However, due to slow manual stripping, production capacity is low, market demand is high, and product quality decreases. This study develops an optimized peeling machine using NIDA-QFD to meet user needs and increase innovation. Experimental design model and 5 alternative actions of cassava peeling machine. ABC Banyuwangi Industry with 10 respondents, including owners and employees, was given intervention in the action decision. NIDA-QFD developed a cassava peeling machine design that is efficient and minimizes risk. Alternative 3 was chosen, with user body dimensions (height 110-180 cm), using sturdy materials (steel angle profile, stainless steel plate), and having 5 peeling rolls (diameter 80 mm, length 910 mm) for an effective and efficient stripping process. The 220 volt 1/2 PK AC drive system ensures the roll rotates with optimal speed and torque. The cassava skin remover is made of stainless steel which is rust-resistant and easy to clean, so it is feasible to overcome the problem of manual peeling of cassava and opportunities for progress in the cassava chips industry.